Sintesis Hidroksiapatit dari Precipitated Calcium Carbonate (PCC) Kulit Telur Ayam Melalui Proses Hidrotermal - Yahya, Muhammad; Azis, Yelmida; Zultiniar, Zultiniar (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Hydroxyapatite Ca10(PO4)6(OH)2 is a calcium phosphate compound which is bioactive ceramic material with high bioafinitas and the principal inorganic constituent of bones and teeth. Hydroxyapatite (HAp) materials used as bone implants, adsorbents and catalysts. In this research synthesis of hydroxyapatite can be made by using material which is rich of CaCO3 like PCC chicken’s egg shell with a composition of 99,45% CaCO3. PCC chicken’s egg shell which has calcium source was synthesized to HAp by hydrothermal process with varied of ratio Ca/P (1,57;1,67;1,77) and reaction temperature (140oC, 160oC, 180oC). HAp synthesized result has been analyzed using X-ray Diffraction (XRD), Scanning Electron Microscopy (SEM) and Fourier Transform Infrared Spectroscopy (FTIR). The results of FTIR analysis, synthesis of HAp with hydrothermal method through precipitated calcium carbonat (PCC) showed the formation of hydroxyapatite in the presence of peaks PO43- dan OH-. The highest peak is obtained at reaction temperature 140oC with ratio Ca/P 1,57 and reaction temperature 160oC with ratio Ca/P 1,67. XRD diffraction results in hydroxyapatite get the highest purity obtained at temperature of 160oC at ratio 1,67 with a hexagonal crystal structures. The results of SEM-EDX analysis, show that the morphological form of agglomerates or clumping . The molar ratio of Ca/ P of hydroxyapatite which is made from chicken’s egg shell through the PCC is 1,69.Keywords: PCC Chicken’s Eggs Shell, pH, Temperature, Hydroxyapatite, Hydrothermal Method.